Safety and efficacy of bosutinib (SKI-606) in chronic phase Philadelphia chromosome–positive chronic myeloid leukemia patients with resistance or intolerance to imatinib - Cortes, Jorge E. (Blood, 2011)
Bosutinib, a dual Src/Abl kinase inhibitor, has shown potent activity against chronic myeloid leukemia (CML). In this phase 1/2 study we evaluated bosutinib in patients with chronic phase imatinib-resistant or imatinib-intolerant CML. Part 1 was a dose-escalation study to determine the recommended starting dose for part 2; part 2 evaluated the efficacy and safety of bosutinib 500 mg once-daily dosing. The study enrolled 288 patients with imatinib-resistant (n = 200) or imatinibintolerant (n = 88) CML and no other previous kinase inhibitor exposure. At 24 weeks, 31% of patients achieved major cytogenetic response (primary end point). After a median follow-up of 24.2 months, 86% of patients achieved complete hematologic remission, 53% had a major cytogenetic response (41% had a complete cytogenetic response), and 64% of those achieving complete cytogenetic response had a major molecular response. At 2 years, progression-free survival was 79%; overall survival at 2 years was 92%. Responses were seen across Bcr-Abl mutants, except T315I. Bosutinib exhibited an acceptable safety profile; the most common treatment-emergent adverse event was mild/moderate, typically self-limiting diarrhea. Grade 3/4 nonhematologic adverse events (> 2% of patients) included diarrhea (9%), rash (9%), and vomiting (3%). These data suggest bosutinib is effective and tolerable in patients with chronic phase imatinib-resistant or imatinib-intolerant CML. This trial was registered at http://www.clinicaltrials.gov as NCT00261846.